Measuring substance use in the club setting: a feasibility study using biochemical markers - Gripenberg-Abdon Johanna; Elgán Tobias H; Wallin Eva; Shaafati Marjan; Beck Olof; Andréasson Sven (BMC, 2012)
Abstract Background During the last few decades the use of club drugs (e.g., cocaine, amphetamines) has been of increased concern in nightlife settings. Traditionally, surveys have been used to estimate the use of club drugs, however, they mostly rely on self-reports which may not be accurate. Recent advances have allowed for readily accessible drug testing methods such as oral fluid drug testing. Nevertheless, research using oral fluid sampling to measure the frequency of drug use in the club environment is scarce. The objective of this study is to evaluate the feasibility of measuring the frequency of alcohol and drug use among Swedish clubbers using breath alcohol and oral fluid drug testing. Method The setting was a 40 hour electronic music dance event (EMDE) on a cruise ship on the Baltic Sea, departing from Sweden, with 875 passengers. Groups of participants at the EMDE were randomly invited to participate. Data were collected with face-to-face and self-administered questionnaires. Further, oral fluid samples were collected to determine illicit drug use, and blood alcohol concentration (BAC) levels were measured using a breath analyzer. Results A total of 422 passengers were asked to participate in the study whereof 21 declined (5.0% refusal rate). Of the 401 study participants (accounting for 45.8% of all attendees), 5 declined oral fluid drug testing. Results show that there was a discrepancy between self-reported and actual drug use as 10.1% of the participants were positive on illicit drug use (amphetamines, ecstasy/MDMA, cannabis, cocaine), while only 3.7% of the participants reported drug use during the last 48 hours. The average BAC level was 0.10% and 23.7% had BAC levels ≥ 0.15%, while 5.9% had levels below the detection limit. The mean BAC levels for the illicit drug users were significantly higher (p = 0.004) than for non-drug users (0.13% vs. 0.10%). Self-reported AUDIT-C scores (using a threshold of ≥ 5 for men and ≥ 4 for women) revealed that 76.0% of the men and 80.7% of the women had risky alcohol consumption patterns. Conclusion This study indicates that it is feasible to conduct breath alcohol and oral fluid drug testing in a Swedish club setting.